STUDI PENERAPAN PRODUKSI BERSIH (STUDI KASUS PADA PERUSAHAAN PULP AND PAPER SERANG) - Nugraha, Winardi Dwi; Susanti, Ina (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2006)
Cleaner produktion is minimization of waste from source. That is can do with some way of likes reuse, reclyle,  recovery  or  house  keeping.  PT.  Indah  Kiat  Pulp  and  Paper  that  location  in Kragilan Village,  Serang  Banten  is  paper  mill  that  in  their  production  aplicated  cleaneer production concept. Action  that  PT.  Indah  Kiat  Pulp  and  Paper  does  in  aplicated  cleaneer production  concept  is recovery  fiber  loss  from  waste  water,  reuse  product  fail  and  house keeping.